Promoting access to higher education in Ghana for human resource development through distance learning - Kankam Boadu (Corresponding; Prof. Sarah Nicholas Oden (University of Cape Coast, 2014)
The idea of using Distance Education (DE) for human resource development is not new in Ghana. It was more vibrant about three decades ago with several unsuccessful attempts. However, the idea resurfaced strongly between 1991 and 1994 that led to the introduction of a number of DE initiatives in all public universities in Ghana. The government had a strong conviction that despite the earlier difficulties, DE was still a viable complement to conventional tertiary education as universities were not able to admit all qualified applicants due to insufficient facilities. The question now is whether this system of education has been able to adequately meet the challenge of providing quality higher education in Ghana. This paper specifically explores how far the University of Cape Coast distance learning programme also known as centre for continuing education has been able to fulfill its mandate. Data was gathered through the use of questionnaire and results were analyzed using simple frequency distribution. Findings indicated that the introduction of the University of Cape Coast Distance Education has widened access to higher education in Ghana
41p,; ill
Keywords: Higher Education; Human Resource Development; Distance Learning/Centre for Continuing Education; Monitoring; Funding; Instructional Materials